The Implementation of Guided Reading Strategy in Teaching English Reading to Slow Learners in Inclusive Junior High Schools - Hafifah Hasyanah Dalimunthe; Rahmah Fithriani (FKIP - Universitas Riau, 2026)
Slow learners in inclusive classrooms often struggle to understand English reading passages, so appropriate reading strategies are needed to support their learning process. This study aims to describe the implementation of Guided Reading strategies in English reading instruction for slow learners in inclusive eighth-grade junior high school classrooms. This study applies a descriptive qualitative methodology with a case study design. The study was conducted in an inclusive junior high school in Indonesia, involving an English teacher selected through purposive sampling. Data were collected through classroom observation and interviews, then analyzed descriptively. The results showed that the Guided Reading strategy was implemented through three main stages, namely pre-reading, during-reading, and post-reading. In the pre-reading stage, the teacher prepared the students by introducing the topic and vocabulary. During the reading stage, the teacher provided step-by-step reading assistance. Furthermore, in the post-reading stage, the teacher helps students understand the content of the reading through simple questions and answers and activities to retell the text. The implementation of this strategy helps slow learners follow the reading process gradually, increases engagement, and builds confidence in learning English reading in inclusive classrooms.